Hubungan Harmonis Antara Manusia, Tuhan, Dan Alam Melalui Tari Sanghyang Penyalin Di Desa Pancasari Kecamatan Sukasada Kabupaten Buleleng (Haridracarya: Journal of Hindu Religious Education, 2023)
This study examines the harmonious relationship between humans, God, and nature through the Sanghyang Penyalin dance in Pancasari Village, Sukasada District, Buleleng Regency. The Sanghyang Penyalin dance is a sacred dance that reflects the teachings of Tri Hita Karana, which teaches balance and harmony between humans and God, fellow humans, and nature. The research method used is qualitative with a descriptive approach. Data were collected through direct observation, interviews with community leaders, artists, and cultural experts, as well as literature studies from various related sources. The results show that the Sanghyang Penyalin dance represents the relationship between humans and God through various rituals and spiritual practices, such as the piuning ceremony and kekidungan, which reflect devotion and supplication to God. This dance also reflects the harmonious relationship between humans and nature, as demonstrated through the yadnya offering ceremony to Bhuta Kala and the use of holy water (tirtha) to maintain ecosystem balance. Additionally, the Sanghyang Penyalin dance strengthens the bonds of brotherhood and mutual cooperation within the community, through the active involvement of all village members in the preparation and performance of the dance, as well as decision-making through joint deliberation. Overall, the Sanghyang Penyalin dance in Pancasari Village is a tangible manifestation of the values of Tri Hita Karana, which teach the importance of maintaining balance and harmony in life. This dance not only has artistic and religious value but also an important social function in preserving nature and strengthening the bonds of brotherhood and mutual cooperation within the community
Keywords: Sanghyang Penyalin Dance; Parahyangan; Pawongan; Palemahan